MEMPERKUAT EKONOMI MASYARAKAT MELALUI EKSISTENSI PARIWISATA ISLAM DI INDONESIA - Zuhud, Muhamad (SIWAYANG Journal: Publikasi Ilmiah Bidang Pariwisata, Kebudayaan, dan Antropologi, 2024)
Indonesia is characterized by its rich multicultural diversity, showcasing a myriad of tribes, cultures, religions, and breathtaking natural beauty that are ripe for exploration. The increasing public interest in leading a healthy and spiritually enriching lifestyle has elevated the role of halal tourism as a prominent industry. Islamic tourism, which adheres to sharia principles, not only offers engaging experiences for visitors but also significantly contributes to the economic empowerment of local communities. The sectors involved in halal tourism, such as hospitality, culinary, and local crafts, see a direct benefit from this growing market. This article explores the positive impacts that Islamic tourism has on enhancing local employment opportunities, boosting small businesses, and fostering cultural exchange. Furthermore, it addresses the challenges faced in promoting halal tourism, including the need for proper infrastructure, awareness among the local population about halal standards, and effective marketing strategies. By understanding these dynamics, stakeholders can work together to advance Islamic tourism in Indonesia, ensuring its sustainability and positive impact on the socio-economic landscape.